Analisis Akuntabilitas Dan Transparansi Pengelolaan Dana Bantuan Operasional Sekolah (Bos) Pada SMK Negeri 1 Klungkung - Putu Liana Anggreni; Ni Putu Yeni Yuliantari (UNHI Press, 2026)
BOS funds are funds used to finance non-personnel costs at primary and secondary education institutions in the implementation of compulsory learning programs, and can support a number of other activities in accordance with the provisions of applicable laws. This study aims to analyze accountability and transparency in the management of School Operational Assistance (BOS) funds at SMK Negeri 1 Klungkung. Data collection was carried out through interviews with several related sources. The steps of data analysis include data collection, data analysis, and drawing conclusions. The results of the analysis show that the management of BOS funds at SMK Negeri 1 Klungkung has gone well and in accordance with Permendikbud No. 2 of 2022. The application of the principle of accountability in the management of BOS Funds at SMK Negeri 1 Klungkung has been carried out well, as reflected in the accountability for the preparation of RKAS, bookkeeping and archiving of transaction evidence, as well as the preparation of realization reports submitted to related parties. However, the application of the principle of transparency in the management of BOS Funds at SMK Negeri 1 Klungkung still needs to be improved, especially in terms of information disclosure to the public and related parties regarding the use of these funds.